Phospholipase A(2) - A structural review - Arni, R. K.; Ward, R. J. (Elsevier B.V., 1996)
Phospholipases A(2) (PLA(2)) are widely distributed in nature and are well characterized proteins with respect to their catalytic and pharmacological activities, A wealth of structural information has recently become available both from X-ray diffraction and NMR studies, and although a detailed model of the catalytic mechanism of PLA(2) has been proposed, the structural bases of other aspects of PLA(2) function, such as interfacial activation and venom PLA(2) pharmacological activities, are still under debate. An appreciation of the PLA(2) protein structure will yield new insights with regard to these activities, the salient structural features of the class I, II and III PLA(2) are discussed with respect to their functional roles. Copyright (C) 1996 Published by Elsevier B.V. Ltd